The smartest giant in town - Donaldson, Julia; Scheffler, Axel (London : MacMillan, 2008)
George the giant, known for wearing his old patched clothes, finally buys new ones, but then gives them away to some needy animals.
K-3.
K-3
Text in Chinese.
Keywords: Animals -- Juvenile fiction; Clothing and dress -- Juvenile fiction; Giants -- Juvenile fiction; Animals -- Fiction; Chinese language materials; Clothing and dress -- Fiction; Giants -- Fiction; Animals -- Fiction; Chinese language; Clothing and dress -- Fiction; Giants -- Fiction